Measuring Disorientation Based on the Needleman-Wunsch Algorithm - Güyer, Tolga; Atasoy, Bilal; Somyürek, Sibel (International Review of Research in Open and Distributed Learning, 2015)
This study offers a new method to measure navigation disorientation in web based systems which is powerful learning medium for distance and open education. The Needleman-Wunsch algorithm is used to measure disorientation in a more precise manner. The process combines theoretical and applied knowledge from two previously distinct research areas, disorientation and string-matching. String-matching algorithms provide a more convenient disorientation measurement than other techniques, in that they examine the similarity between an optimal path and learners’ navigation paths. The algorithm particularly takes into account the contextual similarity between partly relevant web-pages in a user’s navigation path and pages in an optimal path. This study focuses on the reasons and the required steps to use this algorithm for disorientation measurement. Examples of actual student activities and learning environment data are provided to illustrate the process.